2007
DOI: 10.1158/0008-5472.can-07-0177
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glioma Growth in Mice Depleted of Macrophages

Abstract: Macrophages can promote the growth of some tumors, such as those of the breast and lung, but it is unknown whether this is true for all tumors, including those of the nervous system. On the contrary, we have previously shown that macrophages can slow the progression of malignant gliomas through a tumor necrosis factor-dependent mechanism. Here, we provide evidence suggesting that this antitumor effect could be mediated by T lymphocytes, as their number was drastically reduced in tumor necrosis factor-deficient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 27 publications
3
90
0
Order By: Relevance
“…In a glioma model similar to our CD11b-HSVTK model (also using GL261 cells), it previously was suggested that microglia are anti-tumorigenic and that microglia depletion can promote tumor growth (28). However, these findings are based on systemic ganciclovir administration upon bone marrow transplantation including irradiation.…”
Section: Glioma Cells Induce Microglial Mt1-mmp Expression Via Tlr Simentioning
confidence: 86%
“…In a glioma model similar to our CD11b-HSVTK model (also using GL261 cells), it previously was suggested that microglia are anti-tumorigenic and that microglia depletion can promote tumor growth (28). However, these findings are based on systemic ganciclovir administration upon bone marrow transplantation including irradiation.…”
Section: Glioma Cells Induce Microglial Mt1-mmp Expression Via Tlr Simentioning
confidence: 86%
“…The ganciclovir treatment led to a considerable depletion of microglia and to an 80% reduction in glioma volume (Markovic et al, 2009). Using the similar mouse model, Galarneau et al (2007) injected ganciclovir i.p. twice daily for 6 days starting 7 days after tumor implantation.…”
Section: Microglia Promote Glioma Migration and Tumor Growthmentioning
confidence: 99%
“…The CD11b-TK mut-30 model has previously been used to determine the role of proliferating microglia in several mouse models of CNS disease, including cerebral ischemia, gliomas, Alzheimer's disease, CNS viral infection, and axonal regeneration (Carmen et al, 2006;Simard et al, 2006;Galarneau et al, 2007;Lalancette-Hébert et al, 2007;Barette et al, 2008). In all of these paradigms, the selective ablation of proliferating microglia was deleterious.…”
Section: Introductionmentioning
confidence: 99%